Kreativitas Guru dalam Mengembangkan Media Pembelajaran Digital pada Pembelajaran Sejarah Daring (Studi Deskriptif Terhadap Guru Sejarah SMA Di Kota Bandung) - Endah Febriyanti; Yani Kusmarni; Tarunasena Ma'mur (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2021)
This research is motivated by the findings of researcher at the research location which show that in the online history learning process, teacher creativity is needed, one of which is in terms of developing digital learning media. So the study in this research is the creativity of teachers in developing digital learning media in online history learning, with the main problem formulation